Role of Weathering Layers on the Alteration Kinetics of Medieval Stained Glass in an Atmospheric Medium. Issue 1656 (22nd August 2014) - Verney-Carron, Aurélie; Michelin, Anne; Gentaz, Lucile; Lombardo, Tiziana; Chabas, Anne; Saheb, Mandana; Ausset, Patrick; Loisel, Claudine
ABSTRACT: In order to model and predict the alteration of medieval potash-containing stained glass, it is necessary to understand the mechanisms of alteration layer formation at the glass surface and its role on the evolution of alteration kinetics. Moreover, the alteration layers observed on stained glasses are particular, as they are often fractured and heterogeneous in terms of thickness, with the appearance of pits and the detachment of scales. Contrary to silicate glasses altered in aqueous environment where the gel layer has a protective role, cracks and scales are harmful to the durability of stained glasses altered in air. In order to address these mechanistic issues, a program of experiments in the laboratory and in the field were performed. The fracturing was shown to be caused by the growth of the alteration layers and amplified by the alternation of humid and dry periods changing the density of hydrated layers. The pitting is initiated by defects at the glass surface and increased in external atmospheric medium as these defects fix the precipitated salts. However, despite fracturing and pitting, the development of an altered layer imposes a diffusive transport of the solution between the external medium and the bulk glass.